2016
DOI: 10.5539/ijms.v8n4p117
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Tourists Perceived Authenticity towards Experience Quality and Behavior Intention of Cultural Heritage in Macao

Abstract: This study is basically an explorative and explanatory research, with the overall purpose to identify, explore and analyze the tourists' perceived authenticity of culture heritage. This study proposes to identify and evaluate the impact of authenticity by tourists' perceptions of culture heritage on their experience quality and behavioral intention, from which implications for the sustainable development of culture heritage tourism can be derived. The results showed that perceived authenticity has a positive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Most prior studies of authenticity investigate its impact in the context of real-world objects such as museums, cultural events, various cities, or heritage sites (Castéran & Roederer, 2013 ; Guttentag, 2010 ; Li et al, 2016 ; Loureiro, 2019 ; Nguyen & Cheung, 2016 ; Schwan & Dutz, 2020 ; Wu et al, 2019 ; T. Zhang et al, 2018 ). For instance, researchers have examined the impact of tourists’ characteristics, motivations, and place attachment on the perception of authenticity by collecting data from tourists who visited Canyon de Chelly National Monument in Arizona in the USA (Budruk et al, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most prior studies of authenticity investigate its impact in the context of real-world objects such as museums, cultural events, various cities, or heritage sites (Castéran & Roederer, 2013 ; Guttentag, 2010 ; Li et al, 2016 ; Loureiro, 2019 ; Nguyen & Cheung, 2016 ; Schwan & Dutz, 2020 ; Wu et al, 2019 ; T. Zhang et al, 2018 ). For instance, researchers have examined the impact of tourists’ characteristics, motivations, and place attachment on the perception of authenticity by collecting data from tourists who visited Canyon de Chelly National Monument in Arizona in the USA (Budruk et al, 2008 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The influence of experience quality on the satisfaction of cultural-heritage tourists has been extensively researched (Chen and Chen, 2010, Li, Shen and Wen, 2016, Nguyen and Cheung, Lee et al, 2016. In all of these studies, it has been shown that the quality of the experience exerts a positive or direct influence on the satisfaction of tourists.…”
Section: Experience Quality and Satisfactionmentioning
confidence: 99%
“…Regarding the authenticity variable, Li, Shen, and Wen (2016) analysed the relationship between this variable and the quality of experience in the context of cultural tourism. This study considered the authenticity variable as a one-dimensional construct.…”
mentioning
confidence: 99%
“…There are some findings in the existing literature on the relationship between authenticity and experience quality. For example, studies by several scholars confirm that perceived authenticity as a one-dimensional variable has a positive impact on experience quality [49,61]. Similarly, Girish and Chen [52] argue that authenticity is a one-dimensional subjective authenticity and confirmed a positive impact on tourists' holiday experience (e.g., emotions).…”
Section: Authenticity and Experience Qualitymentioning
confidence: 96%